MRC5 and QU-DB bystander cells can produce bystander factors and induce radiation bystander effect - Toossi, Mohammad Taghi Bahreyni (Medknow Publications & Media Pvt Ltd, 2014)
Radiation damages initiated by radiation-induced bystander effect (RIBE) are not limited to the first or immediate neighbors of the irradiated cells, but the effects have been observed in the cells far from the irradiation site. It has been postulated that bystander cells, by producing bystander factors, are actively involved in the propagation of bystander effect in the regions beyond the initial irradiated site. Current study was planned to test the hypothesis. MRC5 and QU-DB cell lines were irradiated, and successive medium transfer technique was performed to induce bystander effects in two bystander cell groups. Conditioned medium extracted from the target cells was transferred to the bystander cells (first bystander cells). After one hour, conditioned medium was substituted by fresh medium. Two hours later, the fresh medium was transferred to a second group of non-irradiated cells (second bystander cells). Micronucleated cells (MC) were counted to quantify damages induced in the first and second bystander cell groups. Radiation effect was observed in the second bystander cells as well as in the first ones. Statistical analyses revealed that the number of MC in second bystander subgroups was significantly more than the corresponding value observed in control groups, but in most cases it was equal to the number of MC observed in the first bystander cells. MRC5 and QU-DB bystander cells can produce and release bystander signals in the culture medium and affect non-irradiated cells. Therefore, they may contribute to the RIBE propagation.